FAKTOR-FAKTOR YANG MEMPENGARUHI AKUNTABILITAS PENGELOLAAN DANA DESA - Novi Safitri; Jaeni Jaeni (JURNAL ILMIAH EDUNOMIKA, 2024)
The village funds are a source of funding for government administration, development implementation, community development, and community empowerment. These funds are sent from the APBN to the villages through the district or city APBD. Village funds are given to improve infrastructure and it is hoped that the government can advance in all aspects of underdeveloped villages. Good management of village funds can realize the government's hope to advance underdeveloped villages. Testing and analyzing the elements that impact the accountability of village budget management is the goal of this study. The investigation was conducted using quantitative approaches. The data utilized here are primary data collected questionnaires sent out to village officials in the village head office in Jekulo District, Kudus Regency. In order to meet its set criteria, this study used the purposive sampling method. This research makes use of SPSS version 23’s multiple linear regression analysis as its analytical tool. According to the results of the test, the accountability of village fund management is unaffected by siskeudes application, competence, transparency, and local knowledge, but it is positively affected by the internal control system.